Dramaturgical Analysis of Role-players on Telegram - Imtiyaz Wahyu Mutifa; Winda Primasari (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2024)
K-Pop (Korean Pop) culture is very popular among Indonesian people, especially children and teenagers. One of the impacts of the popularity of K-Pop is the emergence of role-play accounts. Role-play is a make-believe game that requires players to imitate a K-pop idol. Someone who plays role-play will be called a role-player. We aimed to analyze the differences between how a role-player act in the role-play world and the real world. This research focuses on Telegram role-players. We applied a qualitative netnographic research design and used a dramaturgical theory as a research approach. The results of this study showed that the role-players used Telegram as their front stages where they managed the impressions according to the role-play personas they chose. In addition, the results of this research showed that the direct message features of the role-players’ Telegram accounts are used as their middle stages while the backstage is their real life. The results suggest that each role-player has a different character from their role-play persona, showing the distinctive differences among the front stage, the middle stage and the backstage.